Pengaruh Perubahan Iklim terhadap Produksi Tanaman Pangan di Provinsi Maluku - Santoso, Agung Budi (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
This study was aimed to determine the impact of climate change on food crops performance in the Maluku province, based on the climatological data from 1995 to 2012, and to find out crop commodities that are adaptable to climate change. This study used four models of trend analysis: linear least square pattern, quadratic, exponential, and moving averages. The results of forecasting were used to estimate food crop production in the year of climate change to determine the impact of climate change on crop production. Results showed that soybean was the most sensitive crop to climate change, it had the biggest impact on production, yield declined on both El Nino (10.7%) and La Nina (11.4%). Paddy which is generally cultivated on the wetlands, El Nino had the smallest effect on a decrease of production of 2.9% and 2.4% increased on the La Nina. Corn production decreased 7.4% on the El Nino and 3.9% increased during the La Nina. Sweet potatoes was the most resistant crop to climate change, the impact was increased production by 2.5% during El Nino. To reduce the impacts of climate changes could be done through some efforts, namely: (1) to identify areas of potential drought, floods, pests and diseases endemic based on climate and soil conditions, (2) to develop prediction techniques, based on weather and climate forecasts to provide early warning to farmers, (3) to prepare and disseminate a package of technology which is able to withstand the adverse conditions of the El Nino and La Nina, including varieties, pest and disease prevention, and production inputs which are easily obtained by farmers, (4) to improve irrigation and drainage channels, mainly on the paddy fields to increase production capacity and to prevent crop failure during the dry season.